Characteristics and controlling factors of glutenite reservoir rock quality of retrogradational fan Delta: A case study of the Upper Wuerhe Formation of the Mahu Sag, the Junggar Basin. Issue 6 (November 2021) - Ma, Yongping; Zhang, Xianwen; Huang, Linjun; Wang, Guodong; Zhang, Han; Pan, Shuxin
The glutenite reservoir rock of the fan delta facies is associated with a complex sedimentary environment and high heterogeneity, and by far the characteristics and controlling factors of the reservoir rock quality have not been well understood. By comprehensively investigating the lithofacies, petrology, physical properties and diagenesis of the Upper Wuerhe Formation of the Mahu Sag, the Junggar Basin, it is concluded that the Upper Wuerhe Formation develops three major groups of lithofacies, totally consisting of 11 sub-types, and reservoir rock properties of different lithofacies are greatly varied. This research shows that the lithofacies attributed to the tractive current and density current have well-sorted rock particles, low mud content, well-developed secondary dissolved pores, and thus high overall reservoir rock quality. On the contrary, the lithofacies based on debris flow and sheet flow, are observed with high mud content, suppressed development of intergranular and dissolved pores, and thus poor reservoir rock quality. The system tract controls the macro variation of the reservoir rock quality. The best quality is found in the highstand system tract, followed by those of the lake transgression and at last lowstand system tracts. The micro variation of the reservoir rock quality is determined by the mud content, rock particle size and dissolution. The muddy matrix mainly damages the pore connectivity, and presents the strongest correlation with permeability. The reservoir rock with concentrated particle sizes and well-sorted particles has quality better than those of reservoir rocks composed of excessively large or small particles. Dissolution effectively improves the storage capability of the reservoir rock, resulting in an average porosity increment by 4.2%.